Journal of the Indian Academy of Geriatrics 2019
DOI: 10.35262/jiag.v15i2.66-74
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and its Association with Geriatric Syndromes and Quality of Life in Older Indian Outpatients – A Cross-sectional Pilot Observational Study

Abstract: Background: Despite the huge clinical impact of sarcopenia, there is very little to no data from Indian subcontinent regarding sarcopenia in older adults. We conducted this study to assess the frequency of sarcopenia in Indian older outpatients and its characteristics and associations with various geriatric syndromes and quality of life in Indian older adults. Methods: 100 participants above the age of 65 years were recruited from the outpatient department of Geriatric Medicine of a tertiary care hospital in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“… 3 An Indian study published in 2019 among outpatients found that 53% had sarcopenia using ASWG 2014 criteria. 10 However, it is noteworthy that most of the research on sarcopenia has included subjects with secondary sarcopenia. A meta‐analysis published in 2020 also concluded that sarcopenia is highly prevalent among older adults with chronic disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 3 An Indian study published in 2019 among outpatients found that 53% had sarcopenia using ASWG 2014 criteria. 10 However, it is noteworthy that most of the research on sarcopenia has included subjects with secondary sarcopenia. A meta‐analysis published in 2020 also concluded that sarcopenia is highly prevalent among older adults with chronic disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study screened the elderly patients (≥ 65 years; n = 100) presenting to the outpatient department of Geriatric Medicine in a tertiary care hospital for sarcopenia [ 34 ]. The study also used known standardized screening questionnaires and tools to assess various geriatric syndromes, cognition and QoL.…”
Section: Sarcopenia As a Syndromementioning
confidence: 99%
“…The study also used known standardized screening questionnaires and tools to assess various geriatric syndromes, cognition and QoL. The study found that osteoporosis, hypothyroidism, and neurological disease were the only comorbidities that correlated positively with sarcopenia [ 34 ]. Of these, only osteoporosis was significantly associated with sarcopenia.…”
Section: Sarcopenia As a Syndromementioning
confidence: 99%
See 2 more Smart Citations